The deposition behavior of SiC : H films deposited using a remote PECVD system with an HMWS precursor and C2H2 dilution gas - Cho, Sung Hyuk; Lee, Young Jin; Choi, Doo Jin; Kim, Tae Song (KOREAN ASSOC CRYSTAL GROWTH, INC, 2007)
Silicon carbide (SiC) is a very attractive material in terms of its mechanical strength, chemical inertness, and other properties for applications in microsystems. SiC:H films were deposited on (100) silicon wafers by a remote plasma enhanced chemical vapor deposition (RPE-CVD) system in the temperature range of 300 degrees C-450 degrees C. Hexamethyldisilane (HAMS) and H-2 gas were used as a precursor and a carrier gas, respectively. CA dilution gas was used in order to increase the carbon content in the films. The plasma power was varied from 200W to 300W. The stoichiometric and bonding properties of deposited films were investigated by an Fourier transform infrared (FTIR) spectrometer and X-ray photoelectron spectroscopy (XPS). The thickness of deposited films was measured by ellipsometry. The growth rate of SiC:H films decreased with an increase of temperature from 300 degrees C to 400 degrees C, however, it increased again at 450 degrees C. The growth rate of films increased with the plasma power for all deposition conditions. As the deposition temperature was increased, the sp(3)/(sp(2)+sp(3)) ratio increased from 0.32 to 0.64, which affected the growth behavior and properties of the films. A higher activation energy and lower potential energy of the sp(3) reaction make the sp(3) reaction dominant consuming more energy as the deposition temperature was increased. This caused a thickness decrease with an increase of deposition temperature.
Keywords: CHEMICAL-VAPOR-DEPOSITION; MECHANICAL-PROPERTIES; AMORPHOUS-CARBON; TEMPERATURE; METHANE; CVD